Presence and predictors of persistent pain among persons who sustained an injury in a road traffic crash. (8th December 2014) - Gopinath, B.; Jagnoor, J.; Nicholas, M.; Blyth, F.; Harris, I.A.; Casey, P.; Cameron, I.D.
Abstract Background There is a paucity of prospective studies with long follow‐up that have examined a wide range of correlates associated with persistent pain outcomes in persons who sustained a mild or moderate injury in a road traffic crash. This study aimed to establish the independent predictors of pain severity over 24 months. Methods A total of 364, 284 and 252 persons with mild/moderate musculoskeletal injuries sustained in a vehicle‐related crash participated in telephone interviews in the subacute phase, and at 12 and 24 months, respectively. The numeric rating scale (NRS) assessed pain severity. Pain‐Related Self‐Statements Scale‐Catastrophizing (PRSS‐Catastrophizing) and the Short Form Orebro Musculoskeletal Pain Screening Questionnaire (OMPSQ) were also administered. Results After multivariable adjustment, each 1 SD increase in Short Form‐12 Physical Component Score (SF‐12 PCS) in the subacute phase was associated with 0.73 (p = 0.002) and 1.11 (p < 0.0001) decrease in NRS scores after 12 and 24 months, respectively. Each unit increase in the PRSS‐Catastrophizing score in the subacute phase was associated with 0.54 (p = 0.001) and 0.43 (p = 0.03) increase in NRS scores 12 and 24 months later, respectively. Subacute phase OMPSQ scores were positively associated with NRS scores at 12‐ and 24‐month follow‐ups (p < 0.0001). Conclusions Self‐perceived physical well‐being, pain‐related work disability and pain catastrophizing could play a role in determining long‐term pain‐related outcomes following traffic‐related injuries.